Accumulation of T-cell-suppressive PD-L1high extracellular vesicles is associated with GvHD and might impact GvL efficacy. Issue 3 (10th March 2023) - Baur, Rebecca; Karl, Franziska; Böttcher-Loschinski, Romy; Stoll, Andrej; Völkl, Simon; Gießl, Andreas; Flamann, Cindy; Bruns, Heiko; Schlötzer-Schrehardt, Ursula; Böttcher, Martin; Schewe, Denis M; Fischer, Thomas; et al.
Abstract : Allogeneic hematopoietic stem cell transplantation (allo-HSCT) represents the only curative treatment option for a number of hemato-oncological disorders. In fact, allo-HSCT is considered as one of the most successful immunotherapies as its clinical efficacy is based on the donor T-cells' capacity to control residual disease. This process is known as the graft-versus-leukemia (GvL) reaction. However, alloreactive T-cells can also recognize the host as foreign and trigger a systemic potentially life-threatening inflammatory disorder termed graft-versus-host disease (GvHD). A better understanding of the underlying mechanisms that lead to GvHD or disease relapse could help us to improve efficacy and safety of allo-HSCT. In recent years, extracellular vesicles (EVs) have emerged as critical components of intercellular crosstalk. Cancer-associated EVs that express the immune checkpoint molecule programmed death-ligand 1 (PD-L1) can suppress T-cell responses and thus contribute to immune escape. At the same time, it has been observed that inflammation triggers PD-L1 expression as part of a negative feedback network. Here, we investigated whether circulating EVs following allo-HSCT express PD-L1 and tested their efficacy to suppress the ability of (autologous) T-cells to effectively target AML blasts. Finally, we assessed the link between PD-L1 levels on EVs to (T-)cell reconstitution, GvHD, and disease relapse. We were able to detect PD-L1 + EVs that reached a peak PD-L1 expression at 6 weeks post allo-HSCT. Development of acute GvHD was linked to the emergence of PD-L1 high EVs following allo-HSCT. Moreover, PD-L1 levels correlated positively with GvHD grade and declined (only) on successful therapeutic intervention. T-cell-inhibitory capacity was higher in PD-L1 high EVs as compared with their PD-L1 low counterparts and could be antagonized using PD-L1/PD-1 blocking antibodies. Abundance of T-cell-suppressive PD-L1 high EVs appears to also impact GvL efficacy as patients were at higher risk for relapse. Finally, patients of PD-L1 high cohort displayed a reduced overall survival.Taken together, we show that PD-L1-expressing EVs are present following allo-HSCT. PD-L1 levels on EVs correlate with their ability to suppress T-cells and the occurrence of GvHD. The latter observation may indicate a negative feedback mechanism to control inflammatory (GvHD) activity. This intrinsic immunosuppression could subsequently promote disease relapse.